ENHANCING DATA PRIVACY AND SECURITY IN MULTI CLOUD ENVIRONMENTS - Md Emran Hossain; Md Farhad Kabir; Abdullah Al Noman; Nipa Akter; Zakir Hossain (CV. Multi Kreasi Media, 2022)
In this study, we present and realize a solution for contributing to the provision of data security and data privacy in a hybrid configuration based Multi Cloud environment. This method combines prevention of independent cloud security attacks and server failures through a Byzantine fault tolerance protocol, a data encoding and decoding mechanism using the Dusky architecture to improve reliability and confidentiality; and Shamir's secret sharing scheme to guarantee data trustworthiness and privacy during storage at the cost of a minor performance implication. They compared the security and privacy of their hybrid approach with well-known protocols such as SAML with proxy encryption and Kerberos, showing the benefits in terms of memory footprint, encryption/decryption time and totaltimetoauthenticate. The experimental results show that our hybrid scheme provides considerable improvements with regard to encryption /decryption time, memory consumption and average precision.